Malakoplakia in the Urinary Bladder of 4 Puppies. Issue 4 (July 2021) - Davis, Katelin L.; Cheng, Liang; Ramos-Vara, José; Sánchez, Melissa D.; Wilkes, Rebecca P.; Sola, Mario F.
Malakoplakia in humans most often affects the urinary bladder and is characterized by inflammation with von Hansemann–type macrophages, with or without Michaelis-Gutmann bodies, and is frequently associated with Escherichia coli infection. We describe the microscopic features of malakoplakia in the urinary bladder of 4 puppies. In all cases, the lamina propria of the urinary bladder was markedly expanded by sheets of large, round to polygonal macrophages with intracytoplasmic, periodic acid-Schiff-positive granules and granular inclusions, and rare Prussian blue–positive inclusions. Macrophages were positive for CD18 and Iba1. In 2 cases, Michaelis-Gutmann bodies were detected with hematoxylin and eosin stain and were best demonstrated with von Kossa stain. E. coli infection was confirmed in 2 cases with bacterial culture or polymerase chain reaction (PCR) and sequencing of the bacterial 16S ribosomal RNA gene. Transmission electron microscopy of one case demonstrated macrophages with abundant lysosomes, phagolysosomes, and rod-shaped bacteria. Microscopic features were similar to human cases of malakoplakia. In dogs, the light microscopic characteristics of malakoplakia closely resemble granular cell tumors and histiocytic ulcerative colitis.